2020
DOI: 10.30657/pea.2020.26.31
|View full text |Cite
|
Sign up to set email alerts
|

Optimal vehicle route schedules in picking up and delivering cargo containers considering time windows in logistics distribution networks: A case study

Abstract: This study describes a pickup and delivery vehicle routing problem, considering time windows in reality. The problem of tractor truck routes is formulated by a mixed integer programming model. Besides this, three algorithms - a guided local search, a tabu search, and simulated annealing - are proposed as solutions. The aims of our study are to optimize the number of internal tractor trucks used, and create optimal routes in order to minimize total logistics costs, including the fixed and variable costs of an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…However, as many studies was shown, that it can also be used to check the achievement of sustainable development goals [35] or prioritizing sustainable urban regeneration in sensitive areas [36], which points to its universality. Based on the literature data [8,9,15,37,38,39,40,41,42,43], the main factors for individual groups of the analysis were determined, i.e. strengths, weaknesses, opportunities, threats.…”
Section: Methodology Of Researchmentioning
confidence: 99%
“…However, as many studies was shown, that it can also be used to check the achievement of sustainable development goals [35] or prioritizing sustainable urban regeneration in sensitive areas [36], which points to its universality. Based on the literature data [8,9,15,37,38,39,40,41,42,43], the main factors for individual groups of the analysis were determined, i.e. strengths, weaknesses, opportunities, threats.…”
Section: Methodology Of Researchmentioning
confidence: 99%
“…Optimizing a process by simulation means building a model that reflects the process and finding the best configuration of input fields that find the best response value (Krynke et al, 2019). Optimization usually consists of maximizing or minimizing a selected parameter (Kaczmar, 2016;Kyncl et al, 2017;Le et al, 2020). After building each simulation model, it should be validated, i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effectiveness of the production planning and scheduling processes, in particular at the stage of simulating virtual models of production systems, depends primarily on the mathematical models and optimization algorithms used (Le et al, 2020). In complex production systems, this efficiency is translated primarily into achieving a lower level of production costs, shorter production cycle times with a simultaneous high efficiency of data processing (Kaczmar, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, more and more often IT solutions appear in the area of tracking, monitoring and visualizing the course of production processes in real time [20,21]. The effectiveness of the production planning and scheduling processes, in particular at the stage of simulating virtual models of a digital factory, depends primarily on the applied mathematical models and optimization algorithms [22]. In complex production systems, this efficiency is translated primarily into achieving a lower level of production costs, shorter production cycle times with high data processing efficiency at the same time.…”
Section: Introductionmentioning
confidence: 99%